EFFECTS OF CIPROFLOXACIN ON SECONDARY OSSIFICATION CENTERS IN JUVENILE WISTAR ALBINO RATS - Channa, Muhammad Aslam; Ashfaq, Muhammad; Sanghi, Sibghatullah; Qureshi, Muhammad Azam; Janjua, Muhammad Zahoor (Journal of Ayub Medical College Abbottabad, 2004)
Background: Administration of quinolone therapy is controversial during juvenile age as stated by earlier workers. The fluroquinolones are currently not indicated for young children, because of the arthropathy and adverse effect on growing cartilage shown by studies. However the effects of ciprofloxacin on secondary ossification centers has remained undocumented. This study is therefore aimed to determine the risk of Ciprofloxacin administration on neonatal skeletal differentiation by a prospective and comparative animal study model using Wistar albino rats. Methods: Ciprofloxacin was administered to newly born Wistar albino rat pups at a dose of 20 mg/kg body weight intraperitoneally twice daily from day-1 to day-14 after birth. These animals were killed by deep ether anaesthesia and fixed in 80% alcohol. They were then bulk stained with Alizarin red and Alcian blue. Finally they were cleared in 4% KOH and stored in glycerin. The fore and hind limbs were disarticulated from the axial skeleton and observed under stereomicroscope for evidence of skeletal differentiation in the form of presence of secondary ossification centers in long hones (left humerus and left femur). The time of appearance of these centers were noted and compared statistically with those in control animals. Results: The study revealed that the skeletal differentiation in long bones was delayed by 2.4 + 0.2 days at both proximal and distal ends in humerus and 2.4 + 0.2 days at proximal end and 2.2 + 0.2 days at distal end of femur in experimental animals as compared with controls. Conclusion: The ciprofloxacin administration during post-natally presents a risk to skeletal differentiation and therefore to its growth upto the age of six weeks is albino rate pups. Key Words: Ciprofloxacin, Bone differentiation, Ossification centers